2016
DOI: 10.31989/ffhd.v6i9.270
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic and Anti-proliferative Activity of High Molecular Weight Pectin and Modified Citrus Pectin

Abstract: Background: Pectin is a heterogeneous polysaccharide mainly present in citrus fruits and has different biological activities.Objective: High molecular weight Citrus Pectin and modified citrus pectin (MCP) were tested for their cytotoxic, anti-proliferative, and anti-oxidant activity.Methods: The cytotoxicity of pectin was studied against HaCaT cell line (human keratinocyte cell line) using Trypan blue method and LDH-cytotoxicity assay. Anti-proliferative activity was assayed using a WST-1 proliferation kit. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Many previous studies have focused on Modified Citrus Pectin (MCP) as Gal-3 inhibitor with the ability of binding to Gal-3 as a ligand and claiming that due to limited solubility in water CP and AP in their naive form are unable to interact with Gal-3. However, the latest studies have reported that Pectin is a water-soluble dietary fiber 53 , and exhibit biological activities, ranging from anti-inflammatory, and anti-microbial activities to cardiovascular protective role 54 . A representative compound GCS-100, is a modified polysaccharide extracted from the peel and pulp of citrus fruits with high pH and temperature treatment, and is a Gal-3 antagonist that inhibits myeloma cell growth in vitro 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have focused on Modified Citrus Pectin (MCP) as Gal-3 inhibitor with the ability of binding to Gal-3 as a ligand and claiming that due to limited solubility in water CP and AP in their naive form are unable to interact with Gal-3. However, the latest studies have reported that Pectin is a water-soluble dietary fiber 53 , and exhibit biological activities, ranging from anti-inflammatory, and anti-microbial activities to cardiovascular protective role 54 . A representative compound GCS-100, is a modified polysaccharide extracted from the peel and pulp of citrus fruits with high pH and temperature treatment, and is a Gal-3 antagonist that inhibits myeloma cell growth in vitro 55 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings remained almost ignored until the second decade of the 2000s, when a number of studies started to report a number of new pectin‐based substances with high bactericidal activity …”
Section: Figurementioning
confidence: 99%
“…In 2015, scholars in Lebanon reported the antibacterial activity of citrus pectin against S. aureus , a virulent pathogen which frequently contaminates food, including milk, cheese, meat, and dairy preparations . Pectin showed the highest antibacterial activity at pH 6 with minimum inhibitory concentration (MIC) values ranging from 0.39 mg mL −1 to 3.125 mg mL −1 …”
Section: Figurementioning
confidence: 99%
“…[37] A noticeable exception was the series of studies carried out by scholars in Lebanon reporting first the significant antibacterial activity of citrus pectin against Gram-negative H. pylori; [20] and then also against S. aureus and E. coli. [21] Using a new form of citrus pectin extracted and isolated from waste citrus peel under acid-free conditions by hydrodynamic cavitation in water followed by freeze drying,freezedrying scholars in Italy first confirmed the broad spectrum activity of pectin against both Gram-positive and Gram-negative ubiquitous pathogens such as S. aureus [33] and and P. aeruginosa. [34] Later, they extended the approach to grapefruit IntegroPectin providing the first insight on the antibacterial mechanism of this new form of pectic material interacting with the cell membrane of S. aureus and P. aeruginosa strains.…”
Section: Discussionmentioning
confidence: 99%
“…Two years later, the same team reported that optimal antibacterial activity against S. aureus and E. coli was observed at pH 6, with MIC values against S. aureus ranging between 0.39 mg/mL and 3.125 mg/mL and minimum bactericidal concentration (MBC) varying in the ample range 3.125–12.5 mg/mL [21] . A lower antibacterial activity was observed against E. coli with MICs of 25 and 50 mg/mL and MBC values ranging between 25 and 50 mg/mL.…”
Section: A Broad‐spectrum Antimicrobialmentioning
confidence: 99%